Perceptions and Effectiveness of Counseling Services Among Fashion Design Students: A Qualitative Analysis - Zulfadhli, Gian Agha; Haqqi, Firhan Aimareno Ilzam; Rachmawan, Faizal Alief; Zamroni, Zamroni; Budianti, Eni; Probowati, Devy (Universitas Negeri Malang, 2024)
This study aims to measure the interest level of 10th-grade students majoring in fashion design in utilizing guidance and counseling services at SMKN 1 Batu. This study identifies the factors influencing students' interest in guidance and counseling services. The method used in this research is descriptive qualitative. The sampling technique used is purposive sampling, and data collection was conducted through interviews and observations. This study employs domain data analysis. The results found that students feel that the implementation of guidance and counseling is ineffective. This is influenced by the guidance and counseling services provided not being tailored to the characteristics of the students, and the need for variations in methods and techniques in delivering guidance and counseling services to increase student participation. Keywords: services; guidance and counseling; student interest